Strategies for Translating Indonesian–Arabic Metaphors in the Song Lyrics of Cinta Sejati (Al-Hubb) - Siti Masyitoh; Rifda Haniefa; Ihwan Rahman Bahtiar; Andri Ilham; Siti Jubaidah; Khambali (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze the types of metaphors and metaphor translation strategies from Indonesian into Arabic in the song lyrics Cinta Sejati by Bunga Citra Lestari and its Arabic version Al-Ḥubb al-Khāliṣ, based on Newmark’s theory. The research employs a descriptive qualitative approach with a text analysis design. The data consist of metaphorical expressions in the Indonesian lyrics as the source language and their equivalents in Arabic as the target language. Data were collected using observation and note-taking techniques, while data analysis involved classifying the types of metaphors and identifying the translation strategies applied. The findings reveal that the metaphors in Cinta Sejati fall into four categories: dead metaphors, cliché metaphors, stock metaphors, and original metaphors, with stock metaphors being the most dominant. No instances of recent metaphors were found. In translating the lyrics into Arabic, the translator employed only three of the seven metaphor translation strategies proposed by Newmark, namely reproducing the same image in the target language, replacing the image with a standard target-language image, and converting the metaphor into sense. The most frequently used strategy was reproducing the same image, particularly for metaphors that are universal and culturally acceptable in Arabic. These findings indicate that metaphor translation in song lyrics requires a balance between semantic equivalence, linguistic naturalness, and aesthetic effect. This study is expected to contribute to research on Indonesian–Arabic metaphor translation and to serve as a reference for teaching the translation of poetic texts.